Cooperative work of longitudinal slab ballast-less track prestressed concrete simply supported box girder under concrete creep and a temperature gradient. (October 2020) - Liu, Peng; Zheng, Zhihui; Yu, Zhiwu
Abstract: To study the effects of concrete creep and temperature gradients on the cooperative working performance of a longitudinal slab ballast-less track prestressed concrete simply supported box girder system (girder-rail system), a girder-rail system model was established based on the ANSYS software. Then, the deformation of the girder-rail system caused by concrete creep and temperature gradient was studied in addition to the normal stress redistribution of the sliding layer and the normal stress variation of the interface between the cement asphalt mortar (CA mortar) and track slab. The results showed that the mid-span creep camber of the box girder under the girder-rail system was smaller than that of the single box girder, to which a uniform load (converted from the ballast-less track system) was applied. Concrete creep and temperature gradients led to the camber deformation of the ballast-less track, and then caused a redistribution of interlayer stress. At 1500 days, the creep camber of the box girder caused the appearance of a void in the sliding layer close to the end of the box girder (approximately 2 m). Voids appeared in the sliding layers at the middle and edge of the base plate under positive and negative temperature gradients, respectively. Under the creep camber of the box girder, tensile stress at the interface between the CA mortar and track slab appeared at the end of the box girder. This tensile stress appeared at the interface in the middle and edge of the track slab under positive and negative temperature gradients, respectively. Under the effects of creep camber of the box girder and temperature gradient, the maximum normal tensile stress of the interface was 264.8 kPa at day 1500, which was less than the normal cohesive strength of the interface and indicated that there was no interface separation.